Developing an ocean governance regime for China-Pakistan economic corridor: a comparison of the marine environmental legislation and policy framework by utilizing CRILL methodology - Shijun Zhang; Qian Wu; M Jahanzeb Butt; Minerva Batool; Muhammad Murad Zaib Butt (Frontiers in Marine Science, 2025)
Bilateralism in ocean governance is a novel concept that can be developed under the existing International Environmental Law (IEL) and United Nations Convention on the Law of the Sea (UNCLOS). This research paper suggested that bilateralism in ocean governance is one of the Agenda of Sustainable Development Goal 14 (SDG 14). This research paper utilized the methodology of a Comprehensive Review of Law and Relevant Literature (CRILL methodology) and developed a theoretical and legal framework for bilateral ocean governance with the elements of capacity building, adaptation, precautionary approach and participation. Under the given elements of CRILL methodology, this paper analyzed and compared the ocean governance mechanisms of China and Pakistan and proposed that under the China-Pakistan Economic Corridor (CPEC) of the Belt and Road Initiative (BRI), these two States can develop a bilateral framework of ocean governance for the protection of the marine environment, preservation of fisheries and mitigation of ocean acidification and sea level rise. The results of the CRILL methodology are presented in the form of a proposal that institutional coordination is essential for the effectiveness of bilateral ocean governance cooperation, which is China’s regional agenda of BRI. Through such development, the two States, China and Pakistan, can share the mutual economic benefits of ocean development and can have a strong voice in the global ocean agenda.